2017
DOI: 10.1111/imm.12842
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow type 2 innate lymphoid cells: a local source of interleukin‐5 in interleukin‐33‐driven eosinophilia

Abstract: T helper type 2 (Th2) cells, type 2 innate lymphoid cells (ILC2s) and eosinophil progenitors have previously been described to produce interleukin-5 (IL-5) in the airways upon allergen provocation or by direct administration of IL-33. Eosinophilic airway inflammation is known to be associated with IL-5-dependent eosinophil development in the bone marrow, however, the source of IL-5 remains unclear. T helper cells, ILC2s and CD34 progenitors have been proposed to be involved in this process, therefore, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 51 publications
5
29
1
Order By: Relevance
“…Our observation that IL-33 can drive IL-5 and CCL24 expression is also supported by another study describing that in eosinophilia of airway inflammation, IL-33stimulated production of IL-5 is accompanied by increased levels of CCL24, but not of CCL11. 47 Despite several reports highlighting the influence of eosinophils on the nature of immune cell infiltrates in various solid tumor models, 12,25,48,49 we observed that IL-33-induced changes in the microenvironment of the CT26 tumors only occurred in CD4 + T cells and Tregs but not M1 macrophages, myeloid derived suppressor cells (MDSCs), CD8 + T or NK cells. In accordance with other studies, 18,19 Tregs slightly increased in CT26 tumors post-IL-33 treatment but this increase was not associated with a higher tumor burden.…”
Section: Discussioncontrasting
confidence: 55%
“…Our observation that IL-33 can drive IL-5 and CCL24 expression is also supported by another study describing that in eosinophilia of airway inflammation, IL-33stimulated production of IL-5 is accompanied by increased levels of CCL24, but not of CCL11. 47 Despite several reports highlighting the influence of eosinophils on the nature of immune cell infiltrates in various solid tumor models, 12,25,48,49 we observed that IL-33-induced changes in the microenvironment of the CT26 tumors only occurred in CD4 + T cells and Tregs but not M1 macrophages, myeloid derived suppressor cells (MDSCs), CD8 + T or NK cells. In accordance with other studies, 18,19 Tregs slightly increased in CT26 tumors post-IL-33 treatment but this increase was not associated with a higher tumor burden.…”
Section: Discussioncontrasting
confidence: 55%
“…Knockout mice for IL-7Ra or the common γ chain cytokine receptor lack mature ILC2s 61 indicating an important role for IL-7 in generating ILC2s in vivo. Both IL-2 and IL-7 have also been reported to help maintain ILC2 survival 13,61 while culture in combination of IL-2 and IL-7 has been used to maintain ILC2s isolated from lung or Lin −ve ILC progenitors from bone marrow 62,63 . Mesenteric fat ILC2s maintained a Lin −ve /CD45 +ve / Sca1 +ve /KLRG1 +ve phenotype characteristic of ILC2s during culture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, eosinophils released eosinophil peroxidase, which caused oxidative damage to alveolar cells [2]. Th2 cells also released excessive IL-5, which induced bone marrow cells to differentiate to mature eosinophils [42,44]. In patients with asthma, tracheal epithelial cells release high amounts of eotaxin, which induces eosinophil migration and infiltration into the lungs [45].…”
Section: Discussionmentioning
confidence: 99%